NETWORKING 2011 workshops International IFIP TC 6 Workshops, PE-CRN, NC-Pro, WCNS, and SUNSET 2011, Held at NETWORKING 2011, Valencia, Spain, May 13, 2011, Revised Selected Papers - Casares-Giner, Vicente; Manzoni, Pietro; Pont, Ana (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed post-conference proceedings of four workshops colocated with NETWORKING 2011, held in Valencia, Spain, in May 2011: the Workshop on Performance Evaluation of Cognitive Radio Networks: From Theory to Reality, PE-CRN 2011, the Network Coding Applications and Protocols Workshop, NC-Pro 2011, the Workshop on Wireless Cooperative Network Security, WCNS 2011, and the Workshop on Sustainable Networking, SUNSET 2011. The 28 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers cover a wide range of topics addressing the main research efforts in the fields of network coding, sustainable networking, security in wireless cooperative networks, and performance evaluation of cognitive radio networks.